TALKING STICK: A STRATEGY FOR STUDENTS’ SPEAKING PERFORMANCE - Ramli Ramli; Fitriawati Fitriawati; Nurul Wardian (Jurnal Pendidikan Sang Surya, 2024)
This study aims to determine the mastery of students' speaking skills by using the talking stick strategy. This study used a quantitative approach with a pre-experimental research design. The researcher selected one class as the research sample and used cluster random sampling to select the research sample. Data analysis used a t-test to compare whether there are similarities and differences after normality and homogeneity tests. The results of this study showed that using the talking stick strategy affects students' speaking ability. Data analysis found that the hypothesis test has a value of 0.00 <0.05, indicating that Ha is accepted while H0 is rejected. The talking stick strategy can affect students' speaking ability. This study interprets that talking sticks can be one of the alternative strategies to create an exciting teaching and learning process in improving students' speaking ability.